Answer:
82
Step-by-step explanation:
f(x) = 5x - 3
g(x) = 2x + 9
f(g(x)) = 5 (2x + 9) - 3 ..... replace x with g(x)
f(g(4)) = 5 * (2 * 4 + 9) -3 = 85 - 3 = 82
Answer:
x= no solution
Step-by-step explanation:
4x-2+x=-2+2x
We first add 4x+x on the left side.
5x-2=2+2x
We then add 2 to both sides.
5x=2x
The answer is no solution because we got no answer out of the equation.
Answer & Explanation:
A stem and leaf plot is used to organize data as they are collected. A stem and leaf plot looks something like a bar graph. Each number in the data is broken down into a stem and a leaf, thus the name. The stem of the number includes all but the last digit.
An explicit formula<span> designates the n</span>th<span> term of the </span>sequence<span>, as an expression of n (where n = the term's location). It defines the </span>sequence<span> as a </span>formula<span> in terms of n.</span>
Uhm I don’t know but hope you find it have a nice day doe! Little one! :)